Innovation on Literacy Habit Program for Madrasah Ibtidaiyah in Surabaya - Evi Fatimatur Rusydiyah; Hernik Farisia; Muhammad Syahru Ahmad (UIN Sunan Ampel Surabaya, 2021)
The improvement of reading competence in Indonesia has not yet reached its maximum point. Indonesia’s achievements in a number of surveys also show poor results. Nevertheless, several cities in East Java have started to initiate the development of the literacy through various programs as an act of reflection on the findings of the previous surveys. In Surabaya, some programs have been initiated by goverment to cultivate literacy such as reading corner book review, book discussion, reading community, and others. These programs are aimed to increase reading interest (reading habit) of children in Surabaya. By using the Community Based Research (CBR) method, this research observed innovation as new programs about reading habit in the 27 Madrasah Ibtidaiyah in Surabaya. The author found that there are five stages of innovation (knowledge, persuasion, decision, implementation, and confirmation) were conducted by Madrasah Ibtidaiyah in Surabaya. The result indicates that all the stages have been done well by the library manager in Madrasah Ibtidaiyah in Surabaya. This can be seen from several aspects such as of the knowledge of the importance of literacy for their students, awareness to change for better future, and a decision to implement some new programs in the development of reading habit